2001
DOI: 10.1002/1521-396x(200111)188:1<355::aid-pssa355>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Mass Transport Regrowth of GaN for Ohmic Contacts to AlGaN/GaN

Abstract: A novel selective area mass transport regrowth technique for n þ -GaN, requiring no Ga or Si precursor, was developed for low resistivity contact formation to AlGaN/GaN HEMTs. Masked samples were reactive ion etched followed by a short anneal in NH 3 and H 2 at 1050-1080 C. During annealing mass transport occurred from large open areas to mask edges and narrow mask openings. Autodoping from the SiO 2 mask provided n-type doping. After depositing Ti/Al/Ni/Au contacts, the contact resistance was measured to 0.3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…In this figure, many island‐like structures are generated and the surface morphology becomes rough. There are some reports about mass transport of GaN and AlGaN during annealing process . However, for the samples shown in Figure , we have confirmed that the configurations of the recess structures, such as the depth or inclined angle at edge of recess, were not changed by the thermal treatment.…”
Section: Resultssupporting
confidence: 58%
“…In this figure, many island‐like structures are generated and the surface morphology becomes rough. There are some reports about mass transport of GaN and AlGaN during annealing process . However, for the samples shown in Figure , we have confirmed that the configurations of the recess structures, such as the depth or inclined angle at edge of recess, were not changed by the thermal treatment.…”
Section: Resultssupporting
confidence: 58%
“…2D layer growth at the p-GaN surface and the trench bottom dominates for large L AP , forming an imprint of the original trench. But also, mass transport from the p-GaN surface to the trench sidewall is occurring, as indicated in gray in Figure 2c [27]. This leads to small sidewall angles, a different surface morphology and a planarization of the trench.…”
Section: Methodsmentioning
confidence: 98%
“…Multiple technologies have been tried, including implantation, 5) multi-channels, 6) and regrown ohmic regions. 7) Some groups also used an n þ GaN cap structure to decrease access resistance, which required annealed ohmic contacts. 8) Rough ohmic edge after annealing prevented further shrinking of the source to drain distance, limiting a further decrease of the access resistance.…”
mentioning
confidence: 99%